Effectiveness of Wire Composite Splints in Managing Pain and Mobility in Different Luxation Injuries of Permanent Anterior Teeth: Wire Composite Splints in Managing Pain - Khan, Sajal; Parveen, Naghma; Ghaffar, Amina; Momin, Tasveeb; Saeed, Aalia; Ali, Mamoona (Pakistan Journal of Health Sciences, 2023)
Permanent teeth are susceptible to luxation injuries. Different methods of splinting have been used for better healing outcomes. Pain relief, mobility and gingival lacerations come out to be better managed when traumatic teeth are splinted for a required time. Objective: To determine the effectiveness of wire composite splints in managing pain and mobility in various luxation injuries. Methods: A count of 85 patients meeting the criteria of inclusion were included in the study that was conducted in Pedodontics department at Nishtar Institute of Dentistry Multan from 15th August 2022 to 15th January 2023 in a duration of 6 months. Patients were assessed for pain relief, comfort, and mobility at day zero and then at 7th and 14th day post splinting with 0.4mm wire and composite splints. Results: Grade I mobility was improved by 75.3 % and grade II and III mobility were improved by 100% at 14th day. On VRS scale moderate to severe pain was improved by 100% and mild one was by 73% on 14th day. These splints were effective in relieving pain and improving mobility at 7th and 14th day post splinting. Chi square test shows insignificant associations between pre and post splint mobility. Conclusions: It comes out that wire composite is not only an easy, at hand and quick method but has made mark for patient comfort, relief of pain, improving and managing mobility of different luxation injuries of young permanent anterior. This popular method of tooth stabilization enjoys its popularity for all the right reasons.